Factors influencing organic carbon decomposition of topsoils from the Brazilian Amazon Basin - Koutika, Lydie-Stella; Choné, T.; Andreux, F.; Burtin, G.; Cerri, C.C. (1999)
The influence of texture and local climate, especially precipitation, on C decomposition was evaluated in topsoils under forest and pastures at different sites located in the western, central, and eastern Brazilian Amazon Basin. Independent of the geographical location and vegetation cover, C decomposition was lower in topsoils of fine texture with a sand/clay ratio of less than 1, compared to topsoils of coarse a texture with a sand/clay ratio ranging from 2 to 8. In the former, the low sand/clay ratio appears to reduce C decomposition. In the latter, besides the effect of the high sand/clay ratio, the local climate, especially the annual precipitation, seems to play an important role in controlling C decomposition.